2016
DOI: 10.1038/srep27513
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Mitochondrial Function: A Small Molecule-mediated Approach to Enhance Glucose Stimulated Insulin Secretion in Cholesterol Accumulated Pancreatic beta cells

Abstract: Dyslipidemia, particularly the elevated serum cholesterol levels, aggravate the pathophysiology of type 2 diabetes. In the present study we explored the relationship between fasting blood sugar and serum lipid parameters in human volunteers which revealed a significant linear effect of serum cholesterol on fasting blood glucose. Short term feeding of cholesterol enriched diet to rodent model resulted in elevated serum cholesterol levels, cholesterol accumulation in pancreatic islets and hyperinsulinemia with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…Thirty minutes after internalization, activated receptor appeared as yellow dots at cytoplasm. The data are similar to what we reported on GLP-1R internalization in our previous papers ( [22] , [28] ) In contrast, in Rab5:S34N mutant expressing cells, at 0 min time point, GLP-1R GFP appears as green rim where as GLP-1Tmr appears as red aggregate in patches. We do not see internalization of the GLP-1-Tmr 30 min post treatment indicating impedence in internalization of the activated receptor.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thirty minutes after internalization, activated receptor appeared as yellow dots at cytoplasm. The data are similar to what we reported on GLP-1R internalization in our previous papers ( [22] , [28] ) In contrast, in Rab5:S34N mutant expressing cells, at 0 min time point, GLP-1R GFP appears as green rim where as GLP-1Tmr appears as red aggregate in patches. We do not see internalization of the GLP-1-Tmr 30 min post treatment indicating impedence in internalization of the activated receptor.…”
Section: Resultssupporting
confidence: 91%
“…Insulin secretion studies from BRIN-BD11 cells were carried out following the method of Asalla et al. [28] using a Millipore Rat/Mouse Insulin ELISA kit (cat no. EZRMI-13K).…”
Section: Methodsmentioning
confidence: 99%
“…(Koh et al ; Klein et al ; Kennedy et al ) Most workers attribute this respiratory impairment not to loss of cyt c , or structurally aberrant mitochondria more generally, but to excess mitochondrial cholesterol poisoning the organelle. This hypothesis is superficially appealing and also consistent with mitochondrial dysfunction induced by cholesterol over‐feeding in hepatic (Domínguez‐Pérez et al ) and pancreatic (Asalla et al ) cells. Perhaps significantly, increased contacts between mitochondria and endosomes, and correspondingly decreased contacts between ER and endosomes, have recently been reported in NPC1‐deficient cells (Höglinger et al ).…”
Section: Npc1supporting
confidence: 65%
“…Moderate levels of cholesterol lead to mitochondrial dysfunction by causing structural and functional aberrations (Asalla et al, 2016 ). Mitochondria are poorly constituted with cholesterol in their lipid bilayers as compared to that of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of cholesterol in mitochondrial membrane interferes with oxidative phosphorylation and anti-oxidant defense that result in the generation of ROS which culminates in cell death (Bosch et al, 2011 ). Further, it was shown that cholesterol induced damage in pancreatic β-cells is channelized through mitochondrial dysfunction (Asalla et al, 2016 ). These studies clearly indicate that hypercholesterolemia can lead to mitochondrial dysfunction that can get manifested in various pathological conditions.…”
Section: Introductionmentioning
confidence: 99%